Quantitative analysis of airway obstruction in lymphangioleiomyomatosis. Issue 1 (2nd July 2020) - Verleden, Stijn E.; Vanstapel, Arno; De Sadeleer, Laurens; Weynand, Birgit; Boone, Matthieu; Verbeken, Erik; Piloni, Davide; Van Raemdonck, Dirk; Ackermann, Maximilian; Jonigk, Danny D.; Verschakelen, Johny; Wuyts, Wim A.
Lymphangioleiomyomatosis (LAM) is a rare, cystic lung disease with progressive pulmonary function loss caused by progressively proliferating LAM cells. The degree of airway obstruction has not been well investigated within the pathogenesis of LAM. Using a combination of ex vivo computed tomography (CT), microCT and histology, the site and nature of airway obstruction in LAM explant lungs was compared with matched control lungs (n=5 each). The total number of airways per generation, total airway counts, terminal bronchioles number and surface density were compared in LAM versus control. Ex vivo CT analysis demonstrated a reduced number of airways from generation 7 on (p<0.0001) in LAM compared with control, whereas whole-lung microCT analysis confirmed the three- to four-fold reduction in the number of airways. Specimen microCT analysis further demonstrated a four-fold decrease in the number of terminal bronchioles (p=0.0079) and a decreased surface density (p=0.0079). Serial microCT and histology images directly showed the loss of functional airways by collapse of airways on the cysts and filling of the airway by exudate. LAM lungs show a three- to four-fold decrease in the number of (small) airways, caused by cystic destruction which is the likely culprit for the progressive loss of pulmonary function. This study demonstrates a 4-fold reduction in the number of airways and terminal bronchioles in end-stage LAM lungs using a combination of CT, microCT and histopathology, compared to a matched control group http://bit.ly/2tBTiJy